Ultra-High-Resolution in vitro MRI Study of Age-Related Brain Subcortical Susceptibility Alteration in Rhesus Monkeys at 9.4 T - Wen, Qingqing; Yang, Hongyi; Li, Jiali; Zhang, Jin; Tong, Haiyang; Ye, Qiong; Zhong, Kai (Frontiers in Aging Neuroscience, 2020)
Iron concentration in the brain has been suggested as a biomarker of pathologic neurodegeneration. However, the iron concentration changes in healthy aging as well. This study aimed to quantify the age-related changes in iron concentration in the gray matter of healthy rhesus monkeys using quantitative susceptibility mapping. Three-dimensional gradient-echo images of 16 female rhesus monkey brains aged between 2 and 26 years were acquired in vitro. The susceptibilities in the brain regions of the caudate nucleus (Cd), putamen (Pt), globus pallidus (Gp), and substantia nigra (Sn) were analyzed. The susceptibility varied across different brain regions, with higher levels in the Gp and Sn. Susceptibilities in all analyzed brain regions were linearly correlated with age, yet the plateau period as observed in human brains was absent. This is the first in vitro report of the age-related variability of susceptibility in the deep gray matter of rhesus monkey brains at 9.4 T, with an isotropic resolution of 150 μm. Awareness of age-related changes in susceptibility is vital for the establishment of a baseline to facilitate the differentiation of pathologic neurodegeneration from healthy aging in non-human primate studies.